Constructed Dialogue as Hermeneutic in Small Group Bible Study. Issue 1 (27th July 2022) - Kraut, Joshua
Abstract : Modern-day readers of the Bible continually strive to bridge what Malley (2004) terms the "historical" and "devotional" horizons of the text: to understand the scriptures contextually and to discern their relevance for daily life. Through a discourse analysis of a contemporary American Bible study's weekly conversations, this investigation reveals a particular discursive strategy, that of animating the voice of biblical characters, as a powerful hermeneutic tool in rendering the ancient text more intelligible and relatable. Voicing biblical characters, an instance of what Tannen (2007) terms "constructed dialogue, " enables contemporary readers to posit different inner mental states, motivations and attitudes of biblical characters which explain their actions while also rendering the narrative more vivid. Additionally, constructed dialogue enables readers to perform potential explanations for troublesome passages without claiming assent to them.